Peran Kepala Sekolah Dalam Meningkatkan Mutu Pendidiikan Agama Islam Di Madarasah Aliyah Muhammadiyah 02 Paciran Lamongan - Subhan Adi Santoso (Jurnal Pendidikan Islam, 2021)
The objectives to be achieved in this study are 1) to determine the role of school principals in improving the quality of Islamic religious education. 2) to find out the efforts of school principals in improving the quality of Islamic religious education. 3) to determine the supporting and inhibiting factors in improving the quality of Islamic religious education at Madarasah Aliyah Muhammadiyah 02 Paciran Lamongan. From the results of the study, it was concluded that the principal tried to improve the quality and knowledge of teachers by holding discussions, trainings, seminars and so on. The principal pays attention to the development of student activities in teaching and learning activities, in this case the principal sees directly what is used by teachers, student activity reports, and student attendance books. The principal also tries to equip school infrastructure and equipment including instructional media needed for the smooth and successful teaching and learning process. Completing library books because it is important for the development of the quality of education. Supporting factors in improving the quality of Islamic religious education are the role of effective school principals, exemplary teachers, outstanding students and human resources.